Seismicity Distribution Near a Subducting Seamount in the Central Ecuadorian Subduction Zone, Space‐Time Relation to a Slow‐Slip Event. Issue 7 (20th July 2018) - Segovia, Mónica; Font, Yvonne; Régnier, Marc; Charvis, Philippe; Galve, Audrey; Nocquet, Jean‐Mathieu; Jarrín, Paul; Hello, Yann; Ruiz, Mario; Pazmiño, Andres
Abstract: A temporary onshore‐offshore seismic network deployed during the 2‐year period of the Observación SISmológica en ECuador project provides a detailed and well‐focused image of the seismicity for magnitudes as low as 2.1 at the Central Ecuadorian subduction zone. During this 2‐year experiment, the shallow and locked subduction patch shows little evidence of background seismicity that instead occurred downdip of the coupled patch at ~20‐km depth. In this region, seismicity is possibly controlled by the crustal faults bounding the sedimentary basin of Manabí and the rheology of the upper plate. The dip angle of the interplate contact zone, defined by a smooth interpolation through the hypocenters of thrust events, is consistent with a progressive increase from 6° to 25° from the trench to 20‐km depth. Offshore, a seismic swarm, concomitant with a slow‐slip event rupturing the highly coupled subduction megathrust, highlights the reactivation of secondary active faults within the thickened crust of the subducting Carnegie Ridge at the leading edge of a large oceanic seamount. Key Points: The microseismicity is well imaged with a temporary and dense onshore‐offshore seismic network in central Ecuador Deep onshore seismicity seems to be controlled by the interface coupling and the rheology of the upper crust An offshore seismic swarm in secondary faults in the oceanic crust accompanies a slow slip